A Novel KERA Mutation in a Case of Autosomal Recessive Cornea Plana With Primary Angle-Closure Glaucoma. Issue 2 (February 2016) - Kumari, Deepa; Tiwari, Ankit; Choudhury, Mahasweta; Kumar, Abhishek; Rao, Aparna; Dixit, Manjusha
Abstract : Purpose: Keratocan is a cornea-specific keratan sulfate proteoglycan found predominantly in the adult vertebrate eye. In human beings, mutations in keratocan ( KERA ) are associated with autosomal recessive cornea plana (CNA2), which is characterized by a flattened forward convex curvature of the cornea. Here, we report a novel mutation in a case of autosomal recessive bilateral cornea plana presenting with primary angle-closure glaucoma in a 41-year-old woman from Eastern India. Methods: The KERA gene of the patient and her sons was directly sequenced. Results: Mutational analysis of the KERA revealed 2 novel mutations. The first mutation was a 3 base-pair deletion (c.371_373delTCT), leading to the loss of a highly conserved amino acid (p.Phe125del). The second mutation was a base substitution resulting in a silent mutation (c.69G>A). One of her 2 sons carried the homozygous substitution (c.69G>A), whereas the other son was heterozygous (c.69G>R). Conclusions: The mutation that we report here leads to the deletion of a conserved amino acid (p.Phe125del) from the third LRR motif of the keratocan protein, which might lead to an abnormal tertiary structure of the protein, thereby leading to the disease.